Missense mutation (G480C) in the CFTR gene associated with protein mislocalization but normal chloride channel activity - Smit, L.S; Strong,Theresa V; Wilkinson, Daniel J; Macek, Milan; Mansoura, Monique K; Wood, Deborah L; Cole, J.L; Cutting, Garry R; Cohn, Jonathan A; Dawson, David C (Human molecular genetics, 1995)
We have identified a novel CFTR missense mutation associated with a protein trafficking defect in mammalian cells but normal chloride channel properties in a Xenopus oocyte assay. The mutation, a cysteine for glycine substitution at residue 480 (G480C), was detected in a pancreatic insufficient, African-American, cystic fibrosis (CF) patient. G480C was found on one additional CF chromosome and on none of 220 normal chromosomes, including 160 chromosomes from normal African-American individuals. Western blot analysis and immunofluorescence studies revealed that, in 293T cells, the encoded mutant protein was not fully glycosylated and failed to reach the plasma membrane, suggesting that the G480C protein was subject to defective intracellular processing. However, in Xenopus oocytes, a system in which mutant CFTR proteins are less likely to experience an intracellular processing/trafficking deficit, expression of G480C CFTR was associated with a chloride conductance that exhibited a sensitivity to activation by forskolin and 3-isobutyl-1-methylxanthine (IBMX) that was similar to that of wild-type CFTR. This appears to be the first identification of a CFTR mutant with a single amino acid substitution in which the sole basis for disease is mislocalization of the protein.
Keywords: glycin; teplota; Point Mutation; Molecular Sequence Data; membránové proteiny; oocyty; Cells, Cultured; Cyclic AMP-Dependent Protein Kinase RIIbeta Subunit; Humans; Membrane Proteins; zvířata; proteinkinasy závislé na cyklickém AMP, podjednotka RIIbeta; Cystic Fibrosis; imunoblotting; Oocytes; savci; Cyclic AMP; sekvence nukleotidů; bodová mutace; cystická fibróza; Chloride Channels; kultivované buňky; Xenopus laevis; molekulární sekvence - údaje; ženské pohlaví; Glycine; Immunoblotting; Animals; Cysteine; lidé; chloridové kanály; AMP cyklický; Mammals; cystein; Base Sequence; Temperature; Female